1995
DOI: 10.1073/pnas.92.9.3898
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for a hypothalamothalamocortical circuit mediating pheromonal influences on eye and head movements.

Abstract: A method for simultaneous iontophoretic injections of the anterograde tracer Phaseolus vulgaris leukoagglutinin and the retrograde tracer fluorogold was used to characterize in the rat a hypothalamothalamocortical pathway ending in a region thought to regulate attentional mechanisms by way of eye and head movements. The relevant medial hypothalamic nuclei receive pheromonal information from the amygdala and project to specific parts of the thalamic nucleus reuniens and anteromedial nucleus, which then project … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
20
0
2

Year Published

1998
1998
2011
2011

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(24 citation statements)
references
References 28 publications
2
20
0
2
Order By: Relevance
“…RSCagl is reportedly an integral part of a distributed circuitry subserving defensive behaviors (Carvalho-Netto et al, 2010). Swanson and colleagues (Risold and Swanson, 1995;Risold et al, 1997) described reciprocal connections between MO/VO and RSCagl, but less pronounced MO/VO projections to RSCagl than shown here. More recently, however, Shibata and Naito (2008) demonstrated substantial ORB projections to RSCagl (or area 29d) and further showed that MO primarily targets the rostral two-thirds of area 29d and VO the caudal one-third of area 29d.…”
Section: Efferents Of the Medial And Ventral Orbital Corticesmentioning
confidence: 71%
“…RSCagl is reportedly an integral part of a distributed circuitry subserving defensive behaviors (Carvalho-Netto et al, 2010). Swanson and colleagues (Risold and Swanson, 1995;Risold et al, 1997) described reciprocal connections between MO/VO and RSCagl, but less pronounced MO/VO projections to RSCagl than shown here. More recently, however, Shibata and Naito (2008) demonstrated substantial ORB projections to RSCagl (or area 29d) and further showed that MO primarily targets the rostral two-thirds of area 29d and VO the caudal one-third of area 29d.…”
Section: Efferents Of the Medial And Ventral Orbital Corticesmentioning
confidence: 71%
“…proposed that the hypothalamus is organized into three longitudinally aligned functional zones (periventricular, medial, and lateral) and that the medial hypothalamus can be divided into caudal and rostral regions-a caudal zone associated with Papez's circuit and a rostral one primarily involved in reproductive, defensive, and homeostatic behaviors. Risold and Swanson (1995) further suggested that RE may serve a unique role in certain behaviors associated with the medial hypothalamus, namely, mediating olfactory (pheromonal) influences on eye and head movements during orientation. Specifically, they postulated that pheromonal information is transmitted from olfactory structures (and from basomedial amygdala) to nuclei of the medial hypothalamus (mainly to AHN, VMH, PH, and PMd) and from there to RE and to the anteromedial nucleus (AM) of thalamus.…”
Section: Afferents To Re: Functional Significancementioning
confidence: 97%
“…Risold and Swanson (1995) described a circuit mediating olfactory influences on eye and head movements that, in part, involves reciprocal RE connections with lateral aspects of the agranular retrosplenial cortex (RSCagl). They demonstrated moderate RSCagl projections to RE, predominantly targeting the rostral pole of RE.…”
Section: Afferent Projections To Re: Comparisons With Previous Studiesmentioning
confidence: 99%
“…Whereas the PAG appears to influence antipredatory defensive responses (Cezario et al, 2008), the ventral part of the anteromedial thalamic nucleus projects to the lateral retrosplenial area and is thought to be involved in modulating the eye and head movements associated with attentional processes (Risold and Swanson, 1995). In fact, we have shown recently that the PMd influences the activation of its major projecting targets in response to predatory threats (i.e., the PAG and the ventral part of the anteromedial thalamic nucleus) but does not seem to affect the amygdalar sites involved in predator's cue detection (Cezario et al, 2008).…”
Section: Discussionmentioning
confidence: 99%